Propuesta de tipología de corredores para la Estructura Ecológica Principal de Bogotá (2006)
A hierarchical proposal for corridors of the Bogotá MainEcological Structure –EEP- was presented. This approachconsidered classification criteria such as connectivity of protected area system components, landscape matrix, presence / absence of generating areas of either potential or currentsupport environmental services along the connector main axis, and controlling functions of either urban growth or urban uses over elements of the EEP.